A spray-dried, co-processed rice starch as a multifunctional excipient for direct compression - Karnkamol Trisopon (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. A new co-processed, rice starch-based excipient (CS) was developed via a spray-drying technique. Native rice starch (RS) was suspended in aqueous solutions of 10%–15% cross-linked carboxymethyl rice starch (CCMS) and 0.5%–6.75% silicon dioxide (in the form of sodium silicate), before spray drying. The resulting CSs were obtained as spherical agglomerates, with improved flowability. The compressibility study revealed an improved plastic deformation profile of RS, leading to better compaction and tensile strength. The presence of CCMS also ensured a rapid disintegration of the compressed tablets. CS-CCMS:SiO2 (10:2.7), prepared with 10% CCMS, 2.7% silicon dioxide, and 40% solid content, was found to exhibit the best characteristics. Compared to the two commercial DC excipients, Prosolv® and Tablettose®, the flow property of CS-CCMS:SiO2 (10:2.7) was not significantly different, while the tensile strength was 23%: lower than that of Prosolv® but 4 times higher than that of Tablettose® at 196 MPa compression force. The disintegration time of CS-CCMS:SiO2 (10:2.7) tablet (28 s) was practically identical to that of Tablettose® tablet (26 s) and far superior to that of Prosolv® tablet (>30 min). These results show that CSs could potentially be employed as a multifunctional excipient for the manufacturing of commercial tablets by DC.